Photocatalytic Degradation and Chlorination of Azo Dye in Saline Wastewater. - Luk, Mei Kwan (2016)
Textile effluents containing high amount of azo dyes and inorganic salts are largely generated and is one of the major causes of pollution due to its discharge without adequate treatment. In this study, heterogeneous photocatalysis using ZnO photocatalyst and UV-Vis light irradiation was proposed to treat the dye-containing wastewater in saline condition. The photocatalytic experiment was performed using Mordant Orange-1 (MO-1) as the model dye pollutant in the presence of Clions. ZnO photocatalyst was analyzed by XRD, FESEM-EDX and UV-Vis absorption analyses to determine its crystallinity, surface morphology with elemental composition and band gap energy, respectively. The XRD finding showed that ZnO was in hexagonal wurzite phase and the FESEM-EDX analyses exhibited that ZnO has irregular hexagonal shapes. The band gap of ZnO was determined to be 3.17 eV through the UV-Vis absorption analysis. Next, comparison study showed that ZnO has better photocatalytic activity and sedimentation ability than commercial TiO2. Besides, the effect of process parameters on the photocatalytic degradation of MO-1 were investigated and optimized. Under the experimental condition of 200 mM salinity concentration, 2.5 mg/L initial MO-1 concentration and solution pH 5.6, photocatalytic degradation efficiency of MO-1 in saline condition using ZnO achieved 92.37% after 160 minutes of UV-Vis light irradiation. In addition, mineralization study of MO-1 was investigated in terms of COD removal which achieved 67.09% after 240 minutes of light irradiation. Furthermore, kinetic study was performed employing Langmuir-Hinshelwood (L-H) first-order kinetic model. It was found that the kinetic data matched well with the L-H first-order model with the values kL-H and K obtained equal to 0.1726 mg/L•min and 0.0336 L/min.